Symbolic Meaning in Language in the Pinisi Ship Tradition as a Tourist Attraction - Ernawati AB; Rahmawati Rahmawati; Yenny Susanto; I Nyoman Siryayasa (Borong Newinera Publisher, 2026)
The Pinisi ship is a significant cultural icon in Bulukumba Regency, South Sulawesi, representing the maritime heritage and philosophical worldview of the Bugis-Makassar people. This study examines the symbolic meanings embedded in the Pinisi shipbuilding tradition, focusing on rituals, terminology, and structural elements. Using a qualitative ethnographic approach, data were collected through in-depth interviews with Panrita Lopi (master shipbuilders), workers, local leaders, and observations of shipbuilding practices. The results reveal that each stage of construction carries symbolic significance: determining auspicious days reflects sacred time and harmony with the universe; annattak (laying the keel) symbolizes a strong life foundation; kalabiseang represents stages of perfection; anyorong lopi (launching the ship) signifies birth and the beginning of a journey; ammosi (sprinkling oil or animal blood) conveys spiritual transition; and the two masts embody balance, duality, and moral values of siri’ and pacce. The ship’s seven sails denote cosmic perfection and the seven essential human virtues: faith, perseverance, patience, diligence, wisdom, loyalty, and courage. These symbolic meanings demonstrate that Pinisi shipbuilding transcends technical craftsmanship, reflecting local wisdom, spirituality, and social values. Understanding and preserving these symbolic aspects not only enrich cultural heritage but also provide opportunities for culture-based tourism, promoting both educational and economic benefits in the Bulukumba community.